Prostate cancer and therapeutic challenges - Hawsawi, Yousef MohammedRabaa (J Biol Res (Thessalon), 2020)
Prostate cancer (PC) is the most prevalent type of cancer in men worldwide. In Saudi Arabia, the rate of PC is increasing annually. The sex steroid hormones androgens and their receptors have critical roles in PC development and progression. Additionally, apoptosis-related proteins such as heat-shock proteins are vital molecules in PC development. Steroid hormone-deprivation therapies remain the essential treatment for patients with metastatic PCs; however, acquired resistance to hormone deprivation and the transition to PC androgen independence is a major health obstacle. In this review, we aim to detail the roles of androgens, androgen receptors and sex steroid hormones in inducing apoptosis in PC.